Electrochemical investigation of substituted aniline, melamine and formaldehyde based terpolymers as effective corrosion inhibitors for mild steel in 1M hydrochloric acid solution - Verma C.B.; Quraishi M.A.; Ebenso E.E. (My University, 2025)
Three Terpolymers TERP-1, TERP-2 and TERP-3 were synthesized using melamine, formaldehyde and substituted aniline and their inhibitive action on corrosion of mid steel in 1M HCl was studied using electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, linear polarization and gravimetric and weight loss methods. The inhibition efficiency of these inhibitors followed the order TERP-3 > TERP-2 > TERP-1. Among the studied polymers, TERP-3 exhibited the best inhibition efficiency (98%) at 50 ppm).Tafel polarization studied reveals that investigated polymers are mixed type inhibitors. EIS plot indicates that the addition of inhibitor increases the charge-transfer resistance (Rct) and decreases the double-layer capacitance (Cdl) of the corrosion process, These observation reveal that investigated polymers inhibits mild steel corrosion by adsorption mechanism. Various thermo dynamical parameters were also calculated to substantiate the mechanism of adsorption. © 2014 The Authors.